Pengaruh Covid-19 Terhadap Kesehatan Mental Masyarakat Di Kota Malang - Setyaningrum, Wahyu; Yanuarita, Heylen Amildha (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
It is undeniable that the presence of the COVID-19 pandemic has a major impact on public health. Not only from a physical point of view, but also psychological health because of the various problems and anxiety that occurs as a result. This study aims to see and find out how COVID-19 affects the mental health of the community, especially in Malang City, East Java. In the research, the writer used descriptive qualitative method assisted by purposive sampling technique. Of course, it is complemented by a simple literature study on various data and documents that already exist and are related to the subject under study. The results of this study show that the COVID-19 pandemic does have an impact on people's mental health, mainly due to high levels of stress due to illness caused by viruses, excessive anxiety, and various other influences.